High‐Performance Doped Silver Films: Overcoming Fundamental Material Limits for Nanophotonic Applications. Issue 19 (20th March 2017) - Zhang, Cheng; Kinsey, Nathaniel; Chen, Long; Ji, Chengang; Xu, Mingjie; Ferrera, Marcello; Pan, Xiaoqing; Shalaev, Vladimir M.; Boltasseva, Alexandra; Guo, L. Jay
Abstract : The field of nanophotonics has ushered in a new paradigm of light manipulation by enabling deep subdiffraction confinement assisted by metallic nanostructures. However, a key limitation which has stunted a full development of high‐performance nanophotonic devices is the typical large losses associated with the constituent metals. Although silver has long been known as the highest quality plasmonic material for visible and near infrared applications, its usage has been limited due to practical issues of continuous thin film formation, stability, adhesion, and surface roughness. Recently, a solution is proposed to the above issues by doping a proper amount of aluminum during silver deposition. In this work, the potential of doped silver for nanophotonic applications is presented by demonstrating several high‐performance key nanophotonic devices. First, long‐range surface plasmon polariton waveguides show propagation distances of a few centimeters. Second, hyperbolic metamaterials consisting of ultrathin Al‐doped Ag films are attained having a homogeneous and low‐loss response, and supporting a broad range of high‐ k modes. Finally, transparent conductors based on Al‐doped Ag possess both a high and flat transmittance over the visible and near‐IR range. Abstract : A high‐performance doped Ag film is demonstrated, which has a continuous film formation down to 6 nm, stability over a long shelf time and at high temperatures, and improved adhesion with substrates—all without degradation in its optical properties. Diverse efficient nanophotonic systems based on this material are shown, including plasmonic interconnects, hyperbolic metamaterials, and transparent electrodes.